COVERAGE OF THE PROBLEM OF PERSONALITY GIFTEDNESS IN THE SPIRITUAL HERITAGE OF THE EAST - Raimberdiyev Asqarjan Asrorovich (American Journals, 2023)
This article describes the analysis of the problem of personal potential in the spiritual heritage of the East.
Keywords: Education, upbringing, ability, capacity, development, attention, will.